Inactivation of receptors for bacteriophage T5 during infection of Escherichia coli B. - Dunn, G B (1977)
During infection of Escherichia coli by bacteriophage T5, the cell surface receptors for the phage were inactivated so that they could not be isolated from the infected cells. A mutant of T5 that could only inject 8% of the T5 DNA did not cause the inactivation.